EMPLOYERS’ LIABILITY FOR STRESS AT WORK DUE TO AN EXCESSIVE WORKLOAD: NEW POINTERS FROM THE UNITED KINGDOM - Marlize van Jaarsveld (Obiter, 2022)
Stress-induced illnesses experienced by employees due to excessive workloads are an alarming problem facing employers in the United Kingdom. Not only are stress-induced illnesses a major cause for concern, but these illnesses have moreover been recognised as the second most common work-related ill-health problem in the UK. Workplaces in South Africa are not shielded from the problematic consequences of the work pressures experienced by employees. So far, these problems have mostly been addressed by utilising the provisions of existing legislation. However, despite the existence of legislation in the UK which deals with safety and health issues in employment, a number of employees have successfully claimed damages from their employers by proving breach of contract. In this article, the possibility of South African employers being held contractually liable for stress-induced illnesses based on the excessive workloads of their employees is analysed from a comparative point of view. It is concluded that contractual liability may very well be a reality should the guidelines which emanated from British case law be followed.